FLUOROSIS PREVALENCE AT DIFFERENT REGIONS OF THE EARTH (LITERATURE REVIEW) - L.F. Kaskova; N.A. Morhun; I.Yu. Vashchenko; O.Yu. Andryanova; O.V. Khmil; N.V. Yanko; A.V. Artemyev (Український стоматологічний альманах, 2024)
The aim of the study is to analyze the literature about the fluorosis prevalence and the factors which lead to dental and bone fluorosis.